The new rules of divorce : twelve secrets to protecting your wealth, health, and happiness - Newman, Jacqueline (Atria Books, 2020)
"Elite New York City divorce attorney Jacqueline Newman is here to help, sharing her secrets from over two decades in the trenches. THE NEW RULES OF DIVORCE: 12 Secrets to Protecting Your Wealth, Health, and Happiness is the first definitive guide for navigating modern divorce, full of advice to help readers: decide whether they are actually ready to get a divorce, protect and secure their finances post-breakup, find the right lawyer (or mediator) for their situation, win the child custody schedule they want, heal and stay sane through a disorienting time"--